AGROECOLOGY AND ITS IMPACT ON AGRICULTURAL SUSTAINABILITY AND CLIMATE CHANGE: EVOLUTION IN CUBA. - Calzada, Kolima Peña; Palau Rodríguez, Carlos Manuel; Beltrán, Yaima Hernández; Rodríguez, Leidy Casimiro; Hurtado, Alexander Calero; Silva Fernandes, Thiago Feliph [UNESP]; Marín, Rubén Viera; Rodríguez, Juan Carlos (Universidad Nacional de Colombia, 2025)
Climate change poses a significant threat to agroecosystems. The rapid growth of the global population has increased the demand for food, which in turn has led to intensive use of chemical fertilizers and pesticides for pest control. However, this practice compromises soil quality and can have devastating consequences for agricultural productivity. In this context, agroecological practices emerge as a viable and preventive strategy to mitigate the effects of climate change, especially in developing countries. In this regard, the present review aims to conceptualize agroecology as a transformative approach to the global crisis, analyze its evolution in Cuba, and determine the main agroecological techniques used in the country, as well as their impact on food production. To achieve these objectives, a Systematic Quantitative Review was conducted, consulting databases such as Web of Science, Scopus, Springer Nature, Frontier, Multidisciplinary Digital Publishing Institute (MDPI), WILEY, Google Scholar, and Taylor and Francis. The findings indicate that agroecology is recognized for its transformative capacity in the face of climate, food, and ecosystem crises. Furthermore, there is a gradual growth of the agroecological approach in Cuba, where the most commonly employed techniques include the application of organic fertilizers, the use of bioproducts, and biological pest control. Nevertheless, it is essential to further promote agroecology through public policies and concrete actions that encourage the adoption of these systems in the country.
LA AGROECOLOGÍA Y SU IMPACTO EN LA SOSTENIBILIDAD AGRÍCOLA Y EL CAMBIO CLIMÁTICO: EVOLUCIÓN EN CUBA
Keywords: agroecological practices; bioproduct; organic matter; sustainability; Sustainable agriculture